Dancing with wolves: Making legal territory in a more-than-human world. (June 2015) - Ojalammi, Sanna; Blomley, Nicholas
Highlights: Stronger connections between geographical studies of animals and law are proposed. The importance of territory to property is articulated. The role of animals in the production of legal territory is noted. Wolf–human interactions in S.W. Finland are explored with reference to the territorial dimensions of property. Abstract: As human codings of animals are often simultaneously legal and spatial, it may be useful to bring together the animal geographies literature and scholarship on legal geography. Through a case study set in southwest Finland, we explore the emergent and fraught entanglements of wolves, humans and sheep, characterizing the attempts at the regulation of the wolf as entailing tense biopolitical calculations between the contradictory legal imperatives of biodiversity and biosecurity. Under the former, the wolf must be made to live; under the latter, it may need to die. These are worked out in and productive of two territorial configurations: the everyday spaces of encounter (real or imagined) between wolf and human, and the propertied territories of sheep farming. While human imperatives and anxieties are clearly central to these spatializations, we also seek to give the wolf its due, noting its important role in the making of legal territories. The coproduction of law and space, we conclude, offers important ethical lessons for humans in their relations to the wolf, as well as directing us to the need for more capacious thinking regarding territory.